Essays in understanding : 1930-1954 - Arendt, Hannah, 1906-1975 1906-1975 (Harcourt Brace, 1994)
Few thinkers have tackled the political horrors and complexities of this century with the insight and passionate intellectual integrity of Hannah Arendt. A philosophic champion of human freedom, she was among the first to draw the now-evident parallel between Nazism and Bolshevism and to identify totalitarianism as a threat inherent to the modern world. Jerome Kohn, Arendt's longtime assistant, has compiled, edited, and annotated her manuscripts for publication, beginning with some of her earliest published work and including essays on Augustine, Rilke, Kierkegaard, and figures of the nineteenth-century "Berlin Salon"; the loyalties of immigrant groups within the United States; the unification or "federation" of Europe; "the German problem"; religion, politics, and intellectual life; the dangers of isolation and careerism in American society; the logical consequences of "scientific" theories of Nature and History; the terror that was the organizing principle of both the Nazi and the Communist states. Two seminal essays have never before been published in complete form: "On the Nature of Totalitarianism: An Essay in Understanding" (1953) and "Concern with Politics in Recent European Philosophical Thought" (1954).